1992
DOI: 10.1016/0014-5793(92)80095-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of an essential yeast gene encoding a proteasomal subunit

Abstract: We present the cloning and sequence of a Saccharomyces cerevfsiae gene, PUP2, which encodes for a proteasomal subanit. The PUP2 protein is similar to other proteasomal components from yeast, as well as from Drosophila and rat. Although not-properly.folded proteins have been implicated to constitute substrates of proteusomes, we show that the accumulation of such proteins does not induce expression of the PUP2 gene.Finally, gcn¢ disruption experiments demonstrate that PUP2 belongs to the class of yeast proteaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Candidates that failed to complement an ada mutation would give rise to diploids that were resistant to GAL4-VP16. Slow (Georgatsou et al, 1992). Therefore, we determined whether the gene complementing the ada4 mutation was indeed GCN5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidates that failed to complement an ada mutation would give rise to diploids that were resistant to GAL4-VP16. Slow (Georgatsou et al, 1992). Therefore, we determined whether the gene complementing the ada4 mutation was indeed GCN5.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA sequences were analyzed using the Blast program (Altschul et al, 1990) and the sequence from the -20) primer matched the yeast sequence for the PUP2 gene (Georgatsou et al, 1992), which lies adjacent to GCN5 GCN5 plasmids pRS316-GCN5 was generated by cutting p5-1,2D with PstI, blunting with T4 polymerase and cutting again with Xliol to get a 1.8 kb fragment. This was cloned into pRS316 cut with Xhol and SimaI.…”
Section: Methodsmentioning
confidence: 99%
“…Similarity scores obtained by pairwise alignment of different human, rat or yeast proteasomal subunits of the same species (often 20-40 % identity) imply that many of the genes belong to the same gene family. Moreover, the significant sequence similarity of the a subunit of the archaebacterial particle (Zwickl et al, 1991) to various subunits of eukaryotic proteasomes suggests that these proteasomal proteins are encoded by a gene family of Zwickl et al, 1991Zwickl et al, 1992Fujiwara et al, 1990Emori et al, 1991Heinemeyer et al, 1991Lee et al, 1992Balzi et al, 1990 Haftter and Fox, 1991 Georgatsou et al, 1992Haass et al, 1990aHaass et al, 1 990b Fujii et al, 1991van Riel and Martens, 1992Fujiwara et al, 1989Tanaka et al, 1 990a Tamura et al, 1990Tanaka et al, 1 990b Kumatori et al, 1990bSorimachi et al, 1990Lilley et al, 1990Aki et al, 1992Martinez and Monaco, 1991Frentzel et al, 1992aTamura et al, 1991De Martino et al, 1991Glynne et al, 1991Kelly et al, 1991Lee et al, 1990 ancient origin. Several gene duplication events may have contributed to the complex subunit composition of eukaryotic proteasomes, pro.bably via selection for a variety of functional requirements, although there are clearly structural constraints on the extent of subunit divergence within the cylindrical molecule.…”
Section: Primary Structures Of Proteasomal Proteinsmentioning
confidence: 99%
“…Gene disruption experiments in yeast have demonstrated that several proteasomal proteins are each encoded by a single copy gene and that some of these genes (YC1, YC7a or Y8, Y7, PRE1, PRS3 and PUP2;Fujiwara et al, 1990;Emori et al, 1991;Heinemeyer et al, 1991;Lee et al, 1992;Georgatsou et al, 1992) are essential for cell proliferation, whereas others are not (e.g. Y13; Emori et al, 1991).…”
Section: Proteasomes and Cell Proliferationmentioning
confidence: 99%
“…Sequence data of rat proteasomes are cited from the references shown in Table I. The sources of sequence data of yeast proteasomes are as follows: PRSl and PRS2 [29], PRS3 [30]; Y7 and Y13 [26]; PREl [23]; PRE2 [271; PRE4 [24] and PUP2 [31]. Identity of rat subunits with their yeast counterparts was determined by computer analysis.…”
Section: Inter-subunit Homology Of Rclo-ii In Rat Proteasomesmentioning
confidence: 99%